Reversible Photo-Switching of Dual-Color Fluorescent Mn-Doped CdS-ZnS Quantum Dots Modulated by Diarylethene Molecules - Yuan, Yucheng; Zhu, Hua; Nagaoka, Yasutaka; Tan, Rui; Davis, Andrew Hunter; Zheng, Weiwei; Chen, Ou (Frontiers in Chemistry, 2019)
Dynamic materials have been given an increased amount of attention in recent years with an expectation that they may exhibit properties on demand. Especially, the combination of fluorescent quantum dots (QDs) and light-responsive organic switches can generate novel photo-switchable materials for diverse applications. In this work, a highly reversible dynamic hybrid system is established by mixing dual-color emitting Mn-doped CdS-ZnS quantum dots (QDs) with photo-switchable diarylethene molecules. We show that the diarylethene 1,2-bis(5-(3,5-bis(trifluoromethyl)phenyl)-2-methylthiophen-3-yl)cyclopent-1-ene (switch molecule 1) performs fabulous photo-switching property (between its open, 1o and closed, 1c forms), and high fatigue resistance in this hybrid system. The emission color switching between blue and pink of the system can be induced mainly by selective quenching/recovering of the Mn- photoluminescence (PL) of the QDs due to the switchable absorbance of the molecule 1. Mechanistic studies show the quenching of bandgap- (BG-) PL to photon reabsorption solely, while the quenching of Mn-PL to Förster resonance energy transfer (FRET) process in addition to photon reabsorption by the diarylethene (1) molecules. This photo-switchable system could be potentially used in applications ranging from self-erasing paper to super-resolution fluorescence imaging.